2017
DOI: 10.1371/journal.pone.0178219
|View full text |Cite
|
Sign up to set email alerts
|

Ectopically expressed Slc34a2a sense-antisense transcripts cause a cerebellar phenotype in zebrafish embryos depending on RNA complementarity and Dicer

Abstract: Natural antisense transcripts (NATs) are complementary to protein coding genes and potentially regulate their expression. Despite widespread occurrence of NATs in the genomes of higher eukaryotes, their biological role and mechanism of action is poorly understood. Zebrafish embryos offer a unique model system to study sense-antisense transcript interplay at whole organism level. Here, we investigate putative antisense transcript-mediated mechanisms by ectopically co-expressing the complementary transcripts dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…At the level of transcription, they can induce promoter methylation ( 16 18 ), recruit histone modifying enzymes ( 19 25 ), directly interfere and block the transcriptional machinery via transcriptional interference ( 26 29 ) or regulate sense mRNA splicing ( 30 – 32 ). Post-transcriptionally, they can bind to their sense mRNA and increase its stability by masking miRNA binding sites ( 33 ) or enhance its translation by recruiting additional factors ( 34 ) or generate endogenous siRNAs from double-stranded sense-antisense-hybrids ( 35 , 36 ). Genome-wide expression analysis of sense-antisense pairs has indicated that these are generally positively correlated ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the level of transcription, they can induce promoter methylation ( 16 18 ), recruit histone modifying enzymes ( 19 25 ), directly interfere and block the transcriptional machinery via transcriptional interference ( 26 29 ) or regulate sense mRNA splicing ( 30 – 32 ). Post-transcriptionally, they can bind to their sense mRNA and increase its stability by masking miRNA binding sites ( 33 ) or enhance its translation by recruiting additional factors ( 34 ) or generate endogenous siRNAs from double-stranded sense-antisense-hybrids ( 35 , 36 ). Genome-wide expression analysis of sense-antisense pairs has indicated that these are generally positively correlated ( 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional generalization of antisense transcripts remains elusive, although intense investigation has been carried out since the report of pervasive antisense transcription in the mouse genome and likeliness of their functionality (Kiyosawa et al, 2003(Kiyosawa et al, , 2005. Anti-correlation of expression between sense and antisense transcripts has been observed in individual gene loci, in some of which disruption of the expression of the antisense or sense transcript affected specific phenotypes (Janowski et al, 2007;Morris et al, 2008;Yu et al, 2008;Watts et al, 2010;Modarresi et al, 2012;Piatek et al, 2017). However, a high-throughput experiment revealed mostly positive correlation between sense and antisense transcript expression (Cawley et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, a high-throughput experiment revealed mostly positive correlation between sense and antisense transcript expression (Cawley et al, 2004). In addition, previous studies have reached a consensus that antisense transcripts form several heterogeneous groups with different functions (Faghihi and Wahlestedt, 2009;Piatek et al, 2017). The clear demarcation of developmental-stage-specific and constitutive fractions of antisense transcripts, the biases of positively and negatively correlated variation in expression of sense and antisense transcripts between different combinations of poly(A)+ and total RNA transcripts, and the location and size of the transcript overlap, support this consensus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strategies to adopt a similar approach in mammalian cells, however, failed almost completely. Only a few cell types, oocytes or certain embryonic cells, seem to tolerate significant levels of dsRNA without triggering an immune response ( Wianny and Zernicka-Goetz, 2000 ; Piatek et al, 2017 ). As a consequence the contribution of Dicer and RNA interference to the processing of natural sense/antisense transcript pairs is controversial.…”
Section: Double-stranded Rna Formationmentioning
confidence: 99%